Morphological variations of lung lobes and fissures: a preliminary study - Mathangasinghe, Yasith (Sri Lanka Journal of Surgery, 2021)
Introduction: Anatomical variations of the lung lobes and fissures have implications in diagnostic radiology and thoracic procedures. The prevalence of these variations is not reported in Sri Lanka. Methods: A cross-sectional study was conducted on cadavers to assess the morphological variations of lung lobes and fissures. The presence and absence of lung lobes and fissures were reported in addition to describing the completeness of the major lung fissures. Results: A total of 24 lungs in 12 cadavers were studied. Inferior accessory fissures were noted in one right and one left lung of two independent cadavers. Two cadavers had no horizontal fissures, and one left lung had an incomplete oblique fissure posteriorly. Azygos lobe was not observed in this study sample. Conclusions: The morphology of lung lobes and fissures demonstrate a notable variability, on par with previous reports. Further studies with a large sample size in our population are necessary for generalizable results
Keywords: Pulmonary; lobes; fissures; anatomy; morphology; cadaveric